THE EFFECT OF OCCUPATIONAL SAFETY AND HEALTH ON EMPLOYEE WORK MOTIVATION (CASE STUDY: PT. TROPICA COCOPRIMA LELEMA) - Samban, Yonatan W. A.; Pangemanan, Sifrid S.; Tulung, Joy E. (Universitas Sam Ratulangi, 2021)
Employees are very influential in the production of a company. Occupational safety and health greatly affect employee work motivation. To get an excellent product requires employees who have good health and also a good workplace in order to motivate employees. The purpose of this study was to describe Occupational Safety, Occupational Health and Employee Work Motivation and to analyze the effect of Occupational Safety and Health on Employee Work Motivation either partially or simultaneously at PT. Tropica Cocoprima Lelema. Respondents studied were permanent employees who had worked for more than 1 year. The population in this study were 100 permanent employees, the sample in this study used purposive sampling. The analyzer uses multiple linear regression. Hypothesis testing used the t test and F test. The results showed that Occupational Safety had a partial effect on Employee Work Motivation and Occupational Health had a partial effect on Employee Work Motivation. Simultaneously, Occupational Safety and Health have a significant effect on Employee Work Motivation.Â Keywords: occupational safety, occupational health, employee work motivation